Optimal dosing regimen of ondansetron oral soluble pellicles for preventing postoperative nausea and vomiting after primary total joint arthroplasty: a randomized controlled clinical trial - Wang, Yinghao; Zhong, Shangjie; Zhao, Long; Zhou, Zongke; Wang, Haoyang (Frontiers in Medicine, 2025)
BackgroundThe widespread use of high-dose antifibrinolytic agents (tranexamic acid) and opioids in total joint arthroplasty (TJA) has highlighted a critical concern: postoperative nausea and vomiting (PONV). Ondansetron, recognized as a cornerstone medication for PONV prevention in clinical guidelines, offers an innovative solution through its oral soluble pellicle (OSP) formulation. We conducted this study to investigate the optimal dosing regimen of ondansetron OSPs for preventing PONV following primary TJA.MethodsThis randomized, controlled, double-masked clinical trial allocated 198 patients to three intervention groups: (1) Preop 16 mg group: Two ondansetron OSPs (16 mg) administered orally 1 h before induction, followed by placebo films at 6 and 12 h postoperatively; (2) 16 + 8 mg group: Two ondansetron OSPs (16 mg) administered preoperatively, followed by one ondansetron OSP (8 mg) at 6 h and one placebo film at 12 h postoperatively; (3) 8 + 8 + 8 mg group: One ondansetron OSP (8 mg) and one placebo film administered preoperatively, followed by one ondansetron OSP (8 mg) at both 6 and 12 h postoperatively. The primary outcome assessed the incidence and severity of PONV within 48 h after TJA. Secondary outcomes included the utilization frequency of rescue metoclopramide and tramadol, along with adverse drug reactions (ADRs).ResultsThe primary outcomes demonstrated that both the Preop 16 mg and 16 + 8 mg groups achieved significantly lower incidences of postoperative nausea compared to the 8 + 8 + 8 mg group, although no statistically significant differences were observed among the three groups in nausea severity (visual analog scale (VAS) scores) or postoperative vomiting frequency. The secondary outcomes showed significantly reduced metoclopramide utilization in the 16 + 8 mg group versus the 8 + 8 + 8 mg group, with a non-significant trend in the Preop 16 mg group, while tramadol usage and ADR rates showed no significant intergroup differences.ConclusionCompared to the 8 + 8 + 8 mg regimen, both the Preop 16 mg and 16 + 8 mg dosing strategies demonstrated superior efficacy. For high-risk patients, the 16 + 8 mg regimen may represent the optimal therapeutic approach.